Healthcare assessment tools—a valid source of data for pre-hospital care? Usability for ensuring medical care in the event of a disaster - Konrad, Robert; Schuster, Denise; Heppner, H. J. (Frontiers in Public Health, 2024)
Introduction: Providing care for vulnerable population groups in the event of a disaster or evacuation is in the interests of those affected, of local authorities, health insurance companies, other insurance companies and the responsible authorities and organizations with security tasks (BOS). Evacuation and supply planning is currently mostly carried out using regionally or locally adapted so-called “isolated or individual solutions” or by means of an individual, time-consuming and usually manual and direct personal data query. Can existing medical health data from healthcare assessment tools provide valid information for the planning of care and care needs in disaster and civil protection? Methods: Research and analysis of suitable and regularly used care assessment tools in the care sector in Germany. Results: The healthcare assessment tools cannot be simply combined. Without adaptation they cannot be used at all or only after concerted efforts to interpret the needs for the care of vulnerable groups in a non-clinical context. Discussion: An improved use of individual medical data in disaster and civil protection offers many advantages in prevention, diagnostics, therapy and care in the context of disaster medicine, and not only from an ethical point of view. Due to the different tactical procedures and care strategies in disaster medicine, the field of acute care must be clearly separated from the area of evacuation and care of vulnerable groups. Currently, only the German Armed Forces (Bundeswehr) offer an internally secured infrastructure that allows all those involved in the care of soldiers to access all important medical data quickly and easily from any location.
CRIS-Team Scopus Importer:2025-04-01
Keywords: care assessment tools; health data; operational planning; resource allocation; vulnerable groups